Papyrus 75 and Papyrus 4 Reconsidered - Rodgers, Peter (Filología neotestamentaria, 2025)
In recent years the dating of some early Christian papyri has been challenged. Brent Nongbri especially has questioned the value of paleographic dating, noting that several papyri, chiefly Papyrus 75, could be placed as confidently in the fourth century as in the second/third. This essay seeks a new criterion for assessing the dates of early Christian manuscripts: Nomina Sacra. The abbreviation/suspension of sacred names began with only the four or five, and gradually expanded to include other words treated in this way. Those papyri with fewer Nomina Sacra should be dated early, whereas those that include an expanded list should be deemed to be later. The staurogram is also important in this calculation. On this reckoning, Papyrus 4 may be placed in the second century, Papyrus 75 in the third.